Genetic diversity of West Nile virus isolated from the tick, Rhipicephalus pulchellus, in Kenya - Lwande, Olivia Wesula; Venter, M.; Lutomiah, J.; Michuki, George N.; Rumberia, C.; Gakuya, F.; Obanda, V.; Tigoi, C.; Odhiambo, C.; Nindo, F.; Sang, R. (Elsevier, 2014)
Background: West Nile virus is a re-emerging infectious disease that has a wide geographical distribution in Africa, parts of Europe, the Middle East, Asia, Australia and the Americas where it causes outbreaks. Although WNV has been isolated in mosquitoes in Kenya, paucity of genetic information exists. Mosquitoes are the traditional vectors for WNV however; the virus has also been isolated from some tick species in North Africa and Europe which could be a means of introduction and spreading of the virus over long distances through migratory birds. North-Eastern province of Kenya has been found to be a major hot spot for arbovirus circulation where arboviruses such as Rift Valley fever (RVFV), WNV and Crimean-Congo hemorrhagic fever have been isolated from vectors and humans. Moreover, some of these viruses such as RVF has been reported to have caused outbreaks in the province. Methods & Materials: In this study ticks were sampled from restrained animal hosts (livestock and wildlife), classified to species and processed in pools of up to 8 ticks per pool. Virus screening was performed by cell culture using Vero cells and RT-PCR. Positive cases were subjected to 454 sequencing. Phylogenetic analysis was carried out to determine the evolutionary relationships of our isolates. Results: Among other viruses, WNV was isolated from a pool of Rhipicephalus pulchellus. Sequence data is available in gene bank and this forms the focus of this report. Comparative analysis with 27 different WNV strains from other regions revealed that our isolate belongs to lineage 1. Conclusion: Overall, phylogenetic analysis based on nucleotide sequences showed that although genetically distinct, the WNV strain obtained in this study clustered relatively closely to virus isolates from Russia, Europe and the United States belonging to lineage 1 of WNV. To our knowledge, this is the first documented isolation of WNV from Rhipicephalus pulchellus. It is plausible that wild migratory birds may have dispersed these lineages among these continents through tick vectors.